Corneal edema after phacoemulsification surgery in patients with type II diabetes mellitus - Shakya, Kiran; Pokharel, S; Karki, KJD; Pradhananga, C; Pokharel, RP; Malla, OK (Nepalese Journal of Ophthalmology, 2013)
Introduction: Corneal edema delays early visual recovery after phacoemulsification surgery in diabetes mellitus. Objective: To compare corneal edema of eyes in patients with type II diabetes mellitus and in non-diabetics after phacoemusification surgery. Materials and methods: A hospital-based, retrospective study involving 96 eyes that underwent phacoemulsification surgery for immature cataract at the Department of Ophthalmology, Kathmandu Medical College Teaching Hospital, Kathmandu, Nepal was carried out. Evaluation was performed of 33 eyes in patients with diabetes mellitus (diabetic group) and of 63 eyes in patients without diabetes mellitus (non-diabetic group). All diabetic patients had controlled blood glucose for at least one week prior to the surgery. The operated eye was examined before surgery and on one day, one week, and one month after surgery. Intraocular pressure was measured on each visit. Main outcome measures: The findings of post-operative corneal edema and visual acuity between the diabetic and non-diabetic groups were studied and compared. Results: There was no difference clinically in any pre-operative corneal examination between the diabetic and non-diabetic groups. The corneal edema after surgery was significantly higher in the diabetic group than in the non-diabetic group (p < 0.001). The number of patients with corneal edema one day and one week after surgery was significantly higher in the diabetic group than in the non-diabetic group (after 1 day, OR = 62.5; 95 % CI = 15.31 - 255.11, p < 0.000) and after 1 week, OR = 6.77; 95 % CI = 1.28 - 35.76, p < 0.006). Conclusion: Corneal edema following phacoemusification surgery in diabetic eyes is likely to be more frequent than in non-diabetic eyes. Nepal J Ophthalmol 2013; 5(10): 230-234 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8734